2021
DOI: 10.1021/acs.inorgchem.0c02027
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Formation vs Photodissociation for Light-Responsive Protic Ruthenium Anticancer Compounds: The Oxygenated Substituent Determines Which Pathway Dominates

Abstract: Ruthenium complexes bearing protic diimine ligands are cytotoxic to certain cancer cells upon irradiation with blue light. Previously reported complexes of the type [(N,N)2Ru­(6,6′-dhbp)]­Cl2 with 6,6′-dhbp = 6,6′-dihydroxybipyridine and N,N = 2,2′-bipyridine (bipy) (1 A ), 1,10-phenanthroline (phen) (2 A ), and 2,3-dihydro-[1,4]­dioxino­[2,3-f]­[1,10]­phenanthroline (dop) (3 A ) show EC50 values as low as 4 μM (for 3 A ) vs breast cancer cells upon blue light irradiation (Inorg. Chem.20177519). Herein, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 54 publications
(118 reference statements)
2
49
0
Order By: Relevance
“…In our past work, we have demonstrated that protonation and deprotonation events (with 3 – 5 ) determine the lipophilic vs . hydrophilic properties (5), the UV‐Vis spectral features (6,7) and whether photodissociation or singlet oxygen formation is the dominant pathway for these ruthenium complexes (8). Many Ru(II) diimine complexes exhibit light‐driven toxicity by producing singlet oxygen in cells (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our past work, we have demonstrated that protonation and deprotonation events (with 3 – 5 ) determine the lipophilic vs . hydrophilic properties (5), the UV‐Vis spectral features (6,7) and whether photodissociation or singlet oxygen formation is the dominant pathway for these ruthenium complexes (8). Many Ru(II) diimine complexes exhibit light‐driven toxicity by producing singlet oxygen in cells (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by a lower energy 3 MLCT state for the basic forms which has been demonstrated computationally and experimentally. This 3 MLCT state can interact with 3 O 2 in solution to generate toxic 1 O 2 (8). While all three of our previously reported compounds ( 3 – 5 ) can generate singlet oxygen, complex 5 is the most photocytotoxic with EC 50 values in the presence of blue light of ~4 μM ( vs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the inherent acidity surrounding cancer cells, Papish and co-workers reported a series of pH-activated PACT agents, which can be activated by light- and pH-triggered ligand dissociation [ 118 , 119 , 120 ]. At a low pH value (pH = 5), complexes 57 – 61 existed in their acidic form, and the quantum yields for photodissociation were higher than in deprotonated form.…”
Section: Ru(ii) Pact Agents With Multiple Functionsmentioning
confidence: 99%
“…Thus, they investigated how synthetic changes to ligands and ligand protonation states can influence the quantum yields for 1 O 2 and photodissociation. Cytotoxicity studies showed that 1 O 2 formation is a more plausible cause of photocytotoxicity [ 120 ].…”
Section: Ru(ii) Pact Agents With Multiple Functionsmentioning
confidence: 99%